THE CHEMISTRY OF DISCOLORATION PROCESS ON ROCK ART IN MAROS-PANGKEP AND LEMBATA - Mu`alliful Ilmi, Moh.
In this study, the chemical analyses were conducted to analyse the discoloration of rock art in Leang Tedongnge, Leang Lompoa and Leang Balangajia sites, Maros-Pangkep Region, South Sulawesi and the Nali Site and Tene Koro Site, Lembata Region, East Nusa Tenggara. The analytical methods applied in this research included the analysis of color index using the PERAHU scale and Nixcolor pro instruments, morphological analysis using an optical microscope, microstructure and elemental distribution using SEM-EDS, elemental composition analysis using XRF, mineral content analysis using XRD and Raman spectroscopy, as well as functional groups and chemical bonds analyses using FTIR and XPS. The results of the study on the Leang Tedongnge showed that the discoloration was due to the presence of a gypsum-based grayish deposit layer on the surface of the rock art. This layer is formed by geological process of the reaction between calcium ions from the rock art material and sulfate ions. This layer lead to the declining of rock art chromaticity of especially on the T3, T1 and T4 samples with chromaticity values of 26.9, 12,3 and 7.5, respectively. XRF characterization results demonstrated that the deposit layer is composed of Ca and S elements. Furthermore, the discoloration of rock art in Leang Lompoa is thought to be attributed to the formation of a charcoal-based black deposit layer. The deposit is derived from burning activities around the rock art site. This finding is indicated by the presence of peaks of D and G Bands at Raman shifts of 1326 cm-1 and 1598 cm-1. Furthermore, in Leang Balangajia, the discoloration process occurs due to a blackish deposit on the surface of the rock art. The layer is composed of whewellite (calcium oxalate) which is demonstrated by Raman peaks of oxalate ion at wavenumbers of 493, 598, and 670 cm-1. Whewellite is formed due to the presence of microorganisms that grow on rock art. Meanwhile, the discoloration on the rock art of the Lembata Region is due to the formation of a yellowish deposit composed of Ca, S, Si, and Al on the surface of the pigment layer. The presence of the elements was shown by XRF and SEM-EDS characterizations. The elements possibly come from clay and gypsum minerals that are geologically formed on the rock art surface. Based on these results, it can be concluded that the causes of discoloration at each site are different and depend on certain factors related to site conditions.